Synergetic effects of surface texturing and solid lubricants to tailor friction and wear – A review. (March 2021) - Rosenkranz, Andreas; Costa, Henara L.; Baykara, Mehmet Z.; Martini, Ashlie
Abstract: Surface texturing and solid lubricants have demonstrated the ability to substantially reduce friction and wear under dry conditions. In recent decades, these two technologies have been combined to leverage the advantages of both for superior tribological performance. This review article first summarizes the state-of-the-art regarding surface texturing and solid lubricants, including soft metals, polytetrafluorethylene, diamond-like carbon and 2D layered materials. Then, the synergy between surface textures and solid lubricants is discussed, with particular emphasis on the underlying mechanisms. Finally, gaps in the existing understanding of these synergies are identified and opportunities for future research are suggested. Graphical abstract: Image 1 Highlights: This review focuses on the combination of surface textures and solid lubricants. The limitations of surface textures and solid lubricants for dry sliding are identified. Soft metals, PTFE, DLC and 2d layered materials as solid lubricants are considered. Synergistic mechanisms between texturing and solid lubricants are discussed. Current short-comings and opportunities for future research are identified.